Tindak Tutur “Bahasa Jaksel” sebagai Komunikasi Kontekstual di Kalangan Generasi Milenial Jakarta - Tandaju, Christina; Koli, Nicodemus (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2024)
Mixing language or South Jakarta language or ‘keminggris’ makes Indonesians lose their identity, they are considered arrogant or like to show off. On the other hand, it is considered a modern personality, more open, positive and educated. This view is the basis of this research with the aim of understanding the meaning of intention in using the South Jakarta language, understanding the language rules and ethical implications in using the South Jakarta language, as well as the ethical effects in expressing the South Jakarta language by its users. Descriptive qualitative research method in the context of contextual communication where there are language games and communication styles which are analyzed from the perspective of communication speech act theory with locutionary, illocutionary and perlocutionary elements. The result is to create ease in connectivity, interaction and communication, for the millennial generation and South Jakarta language speakers to mingle across cultures, nations and countries. The South Jakarta language is also an ‘intermediary’ for everyone, especially its speakers, in terms of motivation, social processes and systems, as well as cooperation to face the challenges of an era that demands fast movement with the right strategies and tactics in the midst of intense competition. The language spoken and spoken in South Jakarta is no longer understood to indicate hierarchy and social status with all its prestige and exclusivity, but is more egalitarian as well as a form of social adaptation.